PENGENALAN PARIWISATA BERKELANJUTAN DAN MANAJEMEN PENGUNJUNG UNTUK KEBERLANJUTAN ATRAKSI WISATA SUMBER BIRU BUMDES BENOWO - Zainul Arifin; Sukmawati Nur Salamah; Devi Nur Cahaya Ningsih; Safarudin Hisyam Tualeka; Syafira Marwa (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Tourism is one of the industries in Indonesia that is considered easy to deploy, especially with the natural resources of the nation. Therefore, many regions in Indonesia develop tourism, utilizing natural resources, through what is called BUMDes as a source of revenue. The same reason goes for the BUMDes Benowo Wonotirto Village in Kab. Jombang. This village has a tourist attraction named Wana Wisata Sumber Biru. Wana Wisata Sumber Biru is located in a homogeneous forest area located in the hills and there is a water spring flow there. Wana Wisata Sumber Biru is one of the mass tourism types that need to be managed properly and delicately. Therefore, this paper aims for helping the management to learn and develop their tourism in order to properly create sustainable tourism and manage their visitors. The utilized method for this community service paper consists of two things. First is the observation is conducted to achieve how tourism works in Wanawisata Sumber Biru. Then, the second method is conducted, which is an interview with the management in order to validate the results of the observation. Moreover, after conducting those two methods, the results indicate that the management of Wana Wisata Sumber Biru is successful to establish their tourism, referring to the principle of economics and socio-culture. However, the management still lacks knowledge about how to manage the environmental aspects and needs to be improved.